2006
DOI: 10.1002/cd.175
|View full text |Cite
|
Sign up to set email alerts
|

Respect, liking, and peer social competence in China and the United States

Abstract: Adults often tell children to "show respect" or "be respectful." But how do children understand the concept of respect, and how does it affect their relationships with peers? Can you respect someone you dislike? Can you like someone you do not respect? How does culture influence children' s understanding and expression of liking and respect? These questions sparked the research reported in this chapter.A great deal of empirical research has established the critical function of children' s social competence in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 24 publications
(34 reference statements)
2
21
0
Order By: Relevance
“…This affects one's cognition, understanding of reality, and subsequent reactions to events (Clore and Huntsinger ; Strohminger et al ), and when in conflict, modulates the intensity of a given dispute. It leads disputants to place primary importance on moral self‐perfection rather than legal vindication (Li ; Li and Fischer ; Watkins and Biggs ), and it is the force that drives individuals to strive to become someone who is respected and accepted by others (Cohen et al ; Hsueh et al ; Li and Fischer ).…”
Section: Exploring Legal Consciousnessmentioning
confidence: 99%
“…This affects one's cognition, understanding of reality, and subsequent reactions to events (Clore and Huntsinger ; Strohminger et al ), and when in conflict, modulates the intensity of a given dispute. It leads disputants to place primary importance on moral self‐perfection rather than legal vindication (Li ; Li and Fischer ; Watkins and Biggs ), and it is the force that drives individuals to strive to become someone who is respected and accepted by others (Cohen et al ; Hsueh et al ; Li and Fischer ).…”
Section: Exploring Legal Consciousnessmentioning
confidence: 99%
“…One manifestation of hostile intent is when children expect to be rejected by others, and when children have this expectation, they tend to behave in more aggressive and hostile ways (Downey, Lebolt, Rincón, & Freitas, 1998). Hostile intent also can be operationalized as the victim interpreting the perpetrator’s intent as being disrespectful (Cohen, Hsueh, Zhou, Hancock, & Floyd, 2006; Stewart, Schreck, & Simons, 2006). Finally, emotional reactions to the situation influence how children interpret situational cues (Lemerise & Arsenio, 2000).…”
Section: The Sip Model and Aggressionmentioning
confidence: 99%
“…Research has already shown that being respected is related to various aspects of children's peer relations across multiple levels. For example, being respected by others and showing respect to others are at the interactional level of social competence, which influence, and are influenced by, other levels, (i.e., individual, relationships, and group; Cohen, Hsueh, Zhou, Hancock, & Floyd, ; Hsueh et al, ; Kuryluk, Cohen, & Audley‐Piotrowski, ). Literature across disciplines supports the finding that being respected by peers is positively related to peer social competence at the individual (Huo & Binning, ), interactional (Langdon & Preble, ), relationship (Hsueh et al, 2005), and group levels (Cohen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, being respected by others and showing respect to others are at the interactional level of social competence, which influence, and are influenced by, other levels, (i.e., individual, relationships, and group; Cohen, Hsueh, Zhou, Hancock, & Floyd, ; Hsueh et al, ; Kuryluk, Cohen, & Audley‐Piotrowski, ). Literature across disciplines supports the finding that being respected by peers is positively related to peer social competence at the individual (Huo & Binning, ), interactional (Langdon & Preble, ), relationship (Hsueh et al, 2005), and group levels (Cohen et al, ). At the individual level, self‐evaluations of being respected positively predict self‐esteem and self‐evaluations of group belonging (Huo, Binning, & Molina, ; Simon & Sturmer, ).…”
Section: Introductionmentioning
confidence: 99%